Different Protocols of Combined Application of Photobiomodulation In Vitro and In Vivo Plus AdiposeDerived Stem Cells Improve the Healing of Bones in Critical Size Defects in Rat Models: Photobiomodulation Plus Stem Cells Improve Bone Healing - Khosravipour, Armin; Mostafavinia, Atarodalsadat; Amini, Abdollah; Gazor, Rouhallah; Zare, Fatemeh; Fallahnezhad, Somaye; Rezaei, Fatemehalsadat; Asgari, Mehrdad; Mohammadian, Fatemeh; Mohsenifar, Zhaleh; et al. (Journal of Lasers in Medical Sciences, 2022)
Introduction: Long bone segmental deficiencies are challenging complications to treat. Hereby, the effects of the scaffold derived from the human demineralized bone matrix (hDBMS) plus human adipose stem cells (hADSs) plus photobiomodulation (PBM) (in vitro and or in vivo) on the catabolic step of femoral bone repair in rats with critical size femoral defects (CDFDs) were evaluated with stereology and high stress load (HSL) assessment methods. Methods: hADSs were exposed to PBM in vitro; then, the mixed influences of hDBMS+hADS+PBM on CSFDs were evaluated. CSFDs were made on both femurs; then hDBMSs were engrafted into both CSFDs of all rats. There were 6 groups (G)s: G1 was the control; in G2 (hADS), hADSs only were engrafted into hDBMS of CSFD; in G3 (PBM) only PBM therapy for CSFD was provided; in G4 (hADS+PBM in vivo), seeded hADSs on hDBMS of CSFDs were radiated with a laser in vivo; in G5 (hADSs+PBM under in vitro condition), hADSs in a culture system were radiated with a laser, then transferred on hDBMS of CSFDs; and in G6 (hADS+PBM in conditions of in vivo and in vitro), laser-exposed hADSs were transplanted on hDBMS of CSFDs, and then CSFDs were exposed to a laser in vivo. Results: Groups 4, 5, and 6 meaningfully improved HSLs of CSFD in comparison with groups 3, 1, and 2 (all, P=0.001). HSL of G5 was significantly more than G4 and G6 (both, P=0.000). Gs 6 and 4 significantly increased new bone volumes of CSFD compared to Gs 2 (all, P=0.000) and 1 (P=0.001 & P=0.003 respectively). HSL of G 1 was significantly lower than G5 (P=0.026). Conclusion: HSLs of CSFD in rats that received treatments of hDBMS plus hADS plus PBM were significantly higher than treatments with hADS and PBM alone and in control groups. DOI: 10.34172/jlms.2022.10.